2017
DOI: 10.1186/s13098-017-0288-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D is associated with metabotropic but not neurotrophic effects of exercise in ovariectomized rats

Abstract: PurposeHere, we studied the beneficial effects of aerobic exercise on metabolic syndrome components, cognitive performance, brain derived neurotrophic factor (BDNF) and irisin in ovariectomized rats with different serum vitamin D (Vit D) status.MethodsEighty female wistar rats were divided into 2 groups of sham operated (sham, n = 8), and ovariectomized (OVX, n = 72). Then OVX were divided into 9 groups of receiving combination of exercise protocol with low dose of Vit D (OVX + EXE + LD), high dose of Vit D (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
6
18
0
Order By: Relevance
“…Also, seasonal variations of sunlight ultraviolet exposure and increasing indoor activities reduced cutaneous synthesis of VD [33]. In line with this finding, Babaei et al reported VD insufficiency in ovariectomized rats [34].…”
Section: Discussionmentioning
confidence: 66%
“…Also, seasonal variations of sunlight ultraviolet exposure and increasing indoor activities reduced cutaneous synthesis of VD [33]. In line with this finding, Babaei et al reported VD insufficiency in ovariectomized rats [34].…”
Section: Discussionmentioning
confidence: 66%
“…Among these, difference in physical activity was the most obvious (p50.002) and showed the least heterogeneity (I 2 50). After selection of supporting evidence, we found that aerobic exercise could successfully induce a variety of metabolic activities, which adjusted serum vitamin D into an optimal level (44). At the same time, studies in Japan found that endurance training suppressed a seasonal decrease in serum 25(OH)D concentrations (45).…”
Section: Discussionmentioning
confidence: 98%
“…Animals were injected intraperitoneally combination of 75 mg/kg ketamine (50 mg/mL; Rotexmedica GmbH, Trittau, Germany) and 5 mg/kg of xylazine (20 mg/mL; ScienceLab, Houston, TX, USA). After complete anesthesia, ovaries were accurately removed through midline incision 21…”
Section: Methodsmentioning
confidence: 99%
“…Body weight, Wc and visceral fats were measured after 14 hours fasting. Wc was measured on the largest zone of the rat abdomen 21. Visceral fats were isolated from surrounding tissues of mesenteric, urogenital and retroperitoneal regions and weighed using a weighing-scale (Doulton) 21.…”
Section: Methodsmentioning
confidence: 99%